2019
DOI: 10.1098/rstb.2018.0314
|View full text |Cite
|
Sign up to set email alerts
|

Armet, an aphid effector protein, induces pathogen resistance in plants by promoting the accumulation of salicylic acid

Abstract: Effector proteins present in aphid saliva are thought to modulate aphid–plant interactions. Armet, an effector protein, is found in the phloem sap of pea-aphid-infested plants and is indispensable for the survival of aphids on plants. However, its function in plants has not been investigated. Here, we explored the functions of Armet after delivery into plants. Examination of the transcriptomes of Nicotiana benthamiana and Medicago truncatula following transgenic expression of Armet or infiltration of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
0
40
0
1
Order By: Relevance
“…Moreover, the unique pattern of the aphid host races in manipulating the host defenses may result from the differentially expressed salivary proteins of aphids, which has important consequences for modifying the cross-talk between SA and JA signaling pathways [36]. A recent study showed that Armet, a salivary protein from A. pisum , can suppress the effective JA pathway through the modification of the SA pathway to benefit the feeding activity of A. pisum [37]. Mp10, a salivary protein from M. persicae , could activate both the JA and SA signaling pathways, which led to the relatively low fecundity upon Nicotiana benthamiana [36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the unique pattern of the aphid host races in manipulating the host defenses may result from the differentially expressed salivary proteins of aphids, which has important consequences for modifying the cross-talk between SA and JA signaling pathways [36]. A recent study showed that Armet, a salivary protein from A. pisum , can suppress the effective JA pathway through the modification of the SA pathway to benefit the feeding activity of A. pisum [37]. Mp10, a salivary protein from M. persicae , could activate both the JA and SA signaling pathways, which led to the relatively low fecundity upon Nicotiana benthamiana [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several aphid effectors have now been shown to contribute to aphid virulence; C002 and Armet from A. pisum and M. persicae , Me10 and Me23 from M. euphorbiae , and Mp1, Mp2, and Mp55 from M. persicae ; but their molecular interactions with the plants have just begun to be revealed (Rodriguez and Bos, 2013; Elzinga et al, 2014; Jaouannet et al, 2014; Rodriguez et al, 2017; Cui et al, 2019). Armet from A. pisum and M. persicae promotes SA accumulation (Cui et al, 2019). Mp1 from M. persicae hampers the Vacuolar Protein Sorting Associated Protein52 (VPS52) in the hosts Arabidopsis and potato.…”
Section: Aphid-induced Plant Genesmentioning
confidence: 99%
“…Nicotiana benthamiana has been used for virus transmission assays, VIGS of M. persicae genes, and transient expression of genes from other species to determine their effects on aphid growth and reproduction (Del Toro et al;Ramsey et al, 2007;Bos et al, 2010;Pitino and Hogenhout, 2013;Casteel et al, 2014;Elzinga et al, 2014;Rodriguez et al, 2014;Krenz et al, 2015;Tzin et al, 2015;Mulot et al, 2016;Mathers et al, 2017;Cui et al, 2019;Worrall et al, 2019). However, experiments of this kind are hampered by the fact that many M. persicae isolates do not perform well on N. benthamiana.…”
Section: Discussionmentioning
confidence: 99%